An Analysis of Slang Words in IT Movie - Munthe, Presly Rosalina; Arifin, M. Bahri; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This research discussed slang words found in the movie entitled It directed by Andy Muschietti. This research aimed to find out the kinds of slang words and to know the function of slang words used in It movie. This research was conducted using a descriptive qualitative method. Regarding the research findings, there were two kinds of slang that have been found from twelve kinds of slang theory by Partridge. They are society slang and public house slang. Meanwhile, the next finding was the function of slang. The writer found that there were six functions of slang in It movie, namely to address, to form intimate atmosphere, to initiate relax conversation, to reveal anger, to humiliate, and to show intimacy. This research was expected to enrich the new English vocabulary used in daily conversation. The writer suggested the further researchers to analyze slang with another theory and use a poem, novel, advertisements, or song as the object of research.